Domain-Specific interactions of HPV16 E2 with TopBP1: Insights from Molecular Docking and Dynamics - Hafsa; Javaid, Momina; Zaroon, Zaroon; Nazar, Mobara; Saleem, Muqaddas; Arooj, Rabia; Hussain, Nazim (Journal of Basic and Emerging Sciences, 2025)
Cervical cancer, a major contributor to worldwide cancer-related deaths, is primarily driven by persistent infections with oncogenic human papillomavirus (HPV) types, most notably HPV16. The viral E2 protein is a master regulator, playing pivotal roles in replication, transcription, and episomal maintenance, largely through interactions with host cellular proteins. A key interaction partner is Topoisomerase IIβ-binding protein 1 (TopBP1), a scaffold protein essential for DNA damage response and genome stability. However, the mechanistic details of E2’s engagement with TopBP1’s individual BRCT domains remain poorly characterized. This study employed an integrated in silico approach to elucidate the molecular basis of HPV16 E2’s transactivation domain (TAD) interaction with all eight BRCT domains of TopBP1. High-confidence structural models were predicted, refined, and rigorously validated. Comprehensive protein-protein docking revealed domain-specific binding profiles, identifying E2-D4 and E2-D7 as the most promising complexes based on binding energy and interfacial interactions. Molecular dynamics simulations and MM-GBSA binding free energy calculations for these complexes demonstrated that E2-D4 forms a stable, hydrophobic-driven complex ideal for structural anchoring, while E2-D7 exhibits dynamic, electrostatically stabilized interactions suited for flexible recruitment. These findings provide unprecedented atomistic insight into the HPV16 E2-TopBP1 interactome, revealing novel domain-specific vulnerabilities that could be targeted to disrupt viral persistence and prevent oncogenic progression.